Connecting the Dots: How Digital Financial Literacy and Locus of Control Drive Financial Success Through Financial Behavior? - Melani Awalia; Maulida Nurul Innayah; Wida Purwidianti; Restu Frida Utami (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2024)
This study aims to determine the effect of digital financial literacy and locus of control on the financial performance of MSMEs with financial behavior as a mediating variable. The sample of this research is MSMEs in Banyumas Regency, Central Java, Indonesia. This study uses a Structural Equation Modeling (SEM) analysis tool based on Partial Least Square (PLS) consisting of inner and outer models. This study used a convenience sampling technique and collected 177 respondents. The findings of this study indicate that digital financial literacy and locus of control have a positive and significant effect on the financial behavior and financial performance of MSMEs. Financial behavior also has a positive and significant impact on improving the financial performance of MSMEs. This study's mediation testing results explain that financial behavior can mediate locus of control and digital financial literacy on financial performance. The research results are based on the theory of planned behavior, which states that human behavior can be influenced by individual intentions or motivations and resources in the form of knowledge and skills that can improve the financial performance of MSMEs. This research contributes to providing recommendations for MSMEs, government and financial institutions to improve digital financial literacy and strengthen the locus of control to encourage better financial performance.